Building business in post-communist Russia, eastern Europe, and Eurasia : collective goods, selective incentives, and predatory states - Duvanova, Dinissa, 1977- (Cambridge University Press, 2013)
"This book examines the development of business interest representation in the postcommunist countries of Eastern Europe and Eurasia. The central argument is that abusive regulatory regimes discourage the formation of business associations. At the same time, poor regulatory enforcement tends to encourage associational membership growth. Academic research often treats special interest groups as vehicles of protectionism and non-productive collusion. This book challenges this perspective with evidence of market-friendly activities of industry associations as well as their benign influence on patterns of public governance. Careful analysis of cross-national quantitative data that spans more than 25 countries, as well as the qualitative examination of the development of business associations in Russia, Ukraine, Kazakhstan, and Croatia, shows that postcommunist business associations function as substitutes for state and private mechanisms of economic governance. They challenge corrupt bureaucracy and contribute to the establishment of effective and predictable regulatory regimes. These arguments and empirical findings put the long-standing issues of economic regulations, public goods, and collective action in a new theoretical perspective"--